535 Private Trauma Lists: A Pragmatic Panacea During This Pandemic. (4th May 2021) - Biggs, A; Moore, E; Zbaeda, M; Shah, K; Keightley, A
Abstract: Introduction: COVID-19 has disrupted the efficiency of hospitals nationwide. Ambulant trauma surgery was minimised to reduce risk of contracting COVID-19. Operating capacity significantly reduced and surgical training dramatically curtailed. Locally, a private hospital has been utilised as a green site with consultant-lead trauma lists. Our aim is to review the safety and efficiency of this service. Method: Patients underwent pre-assessment, COVID-19 swabs and 7 days isolation pre and post-op. Staff also underwent swabbing. Prospectively data was gathered for all patients operated on at this site from 12/05/2020 to 20/08/2020. Records reviewed for readmission, complications and COVID status. A satisfaction questionnaire was sent to trainees who operated at this site. Results: 79 operations were completed during this period. 50 male and 29 female, average age 49, average ASA 2. No complications or COVID-19 infections were recorded. Mean time to theatre was 18 days. Delays to theatre led to 2 complications. 87% of trainees felt training was maintained. Conclusions: Establishing a green site enabled efficient and safe management whilst still facilitating surgical training. This requires clear guidelines for staff and patients. We believe this model can help trauma service provision as the pandemic evolves.